Dual Gene Repertoires for Larval and Adult Shells Reveal Molecules Essential for Molluscan Shell Formation. (31st August 2018) - Zhao, Ran; Takeuchi, Takeshi; Luo, Yi-Jyun; Ishikawa, Akito; Kobayashi, Tatsushi; Koyanagi, Ryo; Villar-Briones, Alejandro; Yamada, Lixy; Sawada, Hitoshi; Iwanaga, Shunsuke; Nagai, Kiyohito; Satoh, Noriyuki; et al.
Abstract: Molluscan shells, mainly composed of calcium carbonate, also contain organic components such as proteins and polysaccharides. Shell organic matrices construct frameworks of shell structures and regulate crystallization processes during shell formation. To date, a number of shell matrix proteins (SMPs) have been identified, and their functions in shell formation have been studied. However, previous studies focused only on SMPs extracted from adult shells, secreted after metamorphosis. Using proteomic analyses combined with genomic and transcriptomic analyses, we have identified 31 SMPs from larval shells of the pearl oyster, Pinctada fucata, and 111 from the Pacific oyster, Crassostrea gigas . Larval SMPs are almost entirely different from those of adults in both species. RNA-seq data also confirm that gene expression profiles for larval and adult shell formation are nearly completely different. Therefore, bivalves have two repertoires of SMP genes to construct larval and adult shells. Despite considerable differences in larval and adult SMPs, some functional domains are shared by both SMP repertoires. Conserved domains include von Willebrand factor type A (VWA), chitin-binding (CB), carbonic anhydrase (CA), and acidic domains. These conserved domains are thought to play crucial roles in shell formation. Furthermore, a comprehensive survey of animal genomes revealed that the CA and VWA–CB domain-containing protein families expanded in molluscs after their separation from other Lophotrochozoan linages such as the Brachiopoda. After gene expansion, some family members were co-opted for molluscan SMPs that may have triggered to develop mineralized shells from ancestral, nonmineralized chitinous exoskeletons.